Circular Built Environment During the Digital Age: A Systematic Review - Kısmet, Burcu; Çolakoğlu, Meryem Birgül (Istanbul Technical University, 2025)
As the effects of the Industrial Revolution have significantly contributed to global climate change and the studies reveal that by 2050, the world's energy demand will double while fossil fuel reserves are projected to deplete. To mitigate the risks associated with exceeding the 1.5°C global warming threshold, international organizations, including the United Nations, as well as governments and NGOs, are implementing strategies aimed at achieving carbon neutrality by mid-century. One such approach involves transitioning from the "take-make-waste" model of the linear economy to the circular economy (CE), which operates on principles of "make-use-reuse-recycle." The AECO (Architecture-Construction-Engineering-Operation) industry, a key driver of global economic activity, plays a central role in this transformation by rethinking and restructuring the AECO industry to align with CE principles. This study examines the intersection of circular economy principles and the built environment through the lens of Industry 4.0. A systematic literature review combining descriptive and bibliometric analysis, covering publications from 2016 to 2024 from Scopus and Web of Science (WoS), was conducted using keywords related to CE, the built environment, and digital technologies. The analysis, performed with VOSviewer, highlights key trends, thematic connections, and potential areas for future research. Digital technologies such as building information modeling (BIM), blockchain, and the Internet of Things (IoT) have emerged as powerful tools to support CE implementation. By enabling resource optimization, reducing waste, and enhancing lifecycle assessments, these technologies facilitate the adoption of sustainable practices within the AECO sector. These studies underscore the importance of advancing frameworks like life cycle assessment (LCA) and cradle-to-cradle (C2C) to support circular transitions in the built environment. Furthermore, the results demonstrate the increasing momentum and global interest in leveraging digitalization to achieve sustainability goals in the sector. This study offers valuable insights for academics, industry professionals, and policymakers by mapping the current state of CE research in the AECO industry and identifying emerging trends. It emphasizes the need for comprehensive frameworks and strategic roadmaps to enable the circular transition of the AECO sector. Future research should focus on deepening interdisciplinary collaboration and integrating CE with related sustainability concepts to enhance understanding and accelerate implementation. By doing so, the AECO industry can make significant contributions toward global carbon neutrality and sustainable development goals.